2010
DOI: 10.1007/s11433-010-0123-0
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the Circumferential Grooves Casing Treatment for transonic compressor flow

Abstract: The stall mechanism of the NASA Rotor 37 is investigated through the analysis of the critical flow structures near the stall under the transonic condition. The performance of the rotor with Circumferential Grooves Casing Treatment (CGCT) is also studied based on the Reynolds-Averaging Navier-Stokes approach. The study finds that stall margin improvement can be achieved without significant penalty on the efficiency for the two CGCT configurations applied. The effects of circumferential grooves on the critical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…In a similar line of findings by a few other researchers [23,24], for grooved cases, reduction in choke flow is observed in the current study too. In order to understand the reason for the decrease of choke flow capacity, mass flux at rotor trailing edge is compared for baseline rotor with solid shroud and grooved shroud.…”
Section: Resultssupporting
confidence: 93%
“…In a similar line of findings by a few other researchers [23,24], for grooved cases, reduction in choke flow is observed in the current study too. In order to understand the reason for the decrease of choke flow capacity, mass flux at rotor trailing edge is compared for baseline rotor with solid shroud and grooved shroud.…”
Section: Resultssupporting
confidence: 93%
“…As a result, the fluid element near the wall can no longer proceed in a forward direction. Several studies have been reported to improve the stalling (or delaying the stall condition) in the compressor and turbine by using circumferential casing grooves which gives a wider operating range and higher power or efficiency [30,36].…”
Section: Wells Turbine Performance Parameters and Stall Delaymentioning
confidence: 99%
“…The filtered Navier-Stokes equations are numerically solved by the in-house general-purpose solver NSAWET [46][47][48]. It is based on FVM with the multi-block structured grid and is fully parallelized with the Message Passing Interface (MPI) library.…”
Section: Governing Equationsmentioning
confidence: 99%